The Calorific Requirements of a Human Theme Park - Schneider, Jason (Journal of Interdisciplinary Science Topics, 2017)
The purpose of this paper is to examine the amount of calorific energy required to operate a roller coaster small enough to fit inside the human body. It was found that relative to the amount of energy in food, a miniaturized roller coaster initially designed to be fairly large would require little energy at only 9.27×10‑10 kcal per day.